Construct validity internal and external AGQ and PTEGQ in Spanish - Ruiz-Juan, Francisco (Anales de Psicología / Annals of Psychology, 2015)
The objective is to analyze the psychometric properties of Achievement Goals Questionnaire (AGQ) and Perceptions of Teachers' Emphasis on Goals Questionnaire (PTEGQ) in Spanish, determining the reliability and construct validity and external validity by understanding that achievement goals and perceived motivational climate in physical education may predict intrinsic motivation and satisfaction in those subjects who exercise at leisure time regularly. Psychometric tests confirm PTEGQ and AGQ have four dimensions that are hypothesized from the original one. It has proved the structural supporting hypothesis that it is based on the principle of compatibility. It has also been demonstrated construct validity and external validity as achievement goals and perceived motivational climate in physical education may predict intrinsic motivation and satisfaction in active subjects. Its reliability has been acceptable